Integrated Magnetics Design for a Full-Bridge Phase-Shifted Converter - Yu-Chen Liu; Cheng-You Xiao; Chien-Chun Huang; Pei-Chin Chi; Huang-Jen Chiu (Energies, 2020)
In this study, an optimization procedure was proposed for the magnetic component of an integrated transformer applied in a center-tap phase-shifted full-bridge converter. To accommodate high power–density 0demand, a transformer and an output inductor were integrated into a magnetic component to reduce the volume of the magnetic material and the primary and secondary windings of the transformer were wound on the magnetic legs to reduce conduction loss attributable to the alternating-current resistor. With a focus on the integrated transformer applied in a phase-shifted full-bridge converter, circuit operation in each time interval was analyzed, and a design procedure was established for the integrated magnetic component. In addition, the manner in which output inductance was affected by the mutual inductance between the transformer and the output inductor in the integrated transformer during various operation intervals was discussed and, to minimize circuit loss, a design optimization procedure for the magnetic core was proposed. Finally, the integrated transformer was applied in a phase-shifted full-bridge converter to achieve an input voltage of 400 V, an output voltage of 12 V, output power of 1.7 kW, an output frequency of 80 kHz, and a maximum conversion efficiency of 96.7%.